'No one has even seen… smelt… or sensed a social licence': Animal geographies and social licence to operate. Issue 96 (November 2018) - Duncan, Elizabeth; Graham, Raewyn; McManus, Phil
Highlights: Contentious visible practices evoke the need for a social licence to operate (SLO). Venue exceptionalism is problematic for horse welfare standards. Many SLOs are geographically restrictive and may exclude participants from debates. Legitimacy, transparency, trust and communication are crucial for a SLO to succeed. Geographically restrictive SLOs in animal-based industries will fail these criteria. Abstract: Traditionally, the concept of SLO has been applied to resource-based industries, when companies seek legitimacy because their practice is seen to cause environmental and/or social harms. Recent use of SLO has extended to animal-based industries to address animal welfare concerns. A framework for discussion of such welfare issues is offered by considering SLO in relation to the Australian thoroughbred racing industry, as an example of an animal-based sporting institution. We focus on the visible issue of whipping horses; exploring how visibility as a factor impacts on four key dimensions of the SLO – legitimacy, trust (procedural), transparency and communication. Concluding, when a SLO is under threat, it is often a result of tension between transparency and communication, which in turn impact trust and legitimacy. Furthermore, our findings illustrate that it is the visibility of practices that are seen to cause 'harm' that have the potential to trigger a tipping point for a SLO. Our conclusions contribute to an understanding of how the ethical framework of human-animal relations is constructed and to debates about the potential and limitations of applying the concept of SLO in a range of animal-based industries.